(untitled) (Educational Knowledge, 2024)
Education is recognized as a social and fundamental right according to the Constitution of the Federative Republic of Brazil of 1988. Its purpose is to ensure access and permanence of students in school, thereby guaranteeing a common formation for the exercise of citizenship and occupational development. These premises, embedded in Brazilian legislation, are closely linked to international policies. Among these policies, the United Nations Global Compact stands out, signed in 2015 through the Agenda 2030, reinforcing the concern and commitment of countries to sustainable development. The fourth Sustainable Development Goal (SDG), seeks to ensure inclusive, equitable, and quality education, promoting opportunities for lifelong learning for all. In this context, the importance of comprehensive education resurfaces, which is encompassed within the sixth goal of the National Education Plan (Law 13.005/2014). The State, at various administrative levels, has taken on the coordination of this full-time comprehensive education policy. The article explores the path and perspectives of the comprehensive education program in the State of Espírito Santo, Brazil. Based on bibliographic research and documentary analysis, the article reflects on normative and theoretical principles, highlighting the positive results identified in the learning and experiences of the students.